Laparoscopic Salpingectomy Regulates The Expression of Endometrial Homeobox Genes (HOXA9, HOXA10, HOXA11, HOXD10) and HOX Transcript Antisense Intergenic RNA in Women with Communicating Hydrosalpinx: A Prospective Study - Fatemeh Zafarani; Malek Soleimani Mehranjani; Firouzeh Ghaffari; Maryam Shahhoseini; Seyed Mohammadi Ali Shariatzadeh (International Journal of Fertility and Sterility)
Background: This study aimed to determine the alteration of endometrial expression levels of HOXA9/HOXA10/HOXA11/HOXD10 genes and HOX transcript antisense intergenic RNA (HOTAIR) in mid-luteal phase endometriumin patients with hydrosalpinx before and after salpingectomy.Materials and Methods: In this prospective study, 14 infertile women with unilateral hydrosalpinx who werescheduled for laparoscopic salpingectomy were evaluated. The presence of hydrosalpinx was confirmed by hysterosalpingographyor transvaginal 2D-ultrasonography. All patients had normal hormonal profiles, body mass index,and regular menstrual cycles identified by mid-luteal serum progesterone. Fourteen healthy fertile age-matchedwomen with a successful pregnancy history were considered the control group. Mid-luteal-phase endometrial biopsieswere performed at the time of surgery and during the mid-luteal phase of the fourth treatment cycle byPipelle. After tissue collection, RNA extraction and cDNA synthesis were performed. Real-time polymerase chainreaction (PCR) technique was used for quantitative gene expression of HOXA9/HOXA10/ HOXA11/ HOXD10 andlnc HOTAIR.Results: The endometrial expression of HOXA9 (P<0.001), HOXA10 (P=0.001), HOXA11 (P=0.003), and HOXD10(P=0.004) were significantly lower in the patients with hydrosalpinx compared to the controls. After salpingectomy,we observed a significant increase in the endometrial HOXA9 (P=0.006) and HOXA10 (P=0.023) mRNA expressionlevels compared to before salpingectomy samples. Similarly, a significant upregulation in endometrial HOXA11 (P=0.013) and HOXA10 mRNA expression levels (P=0.012) were detected in postoperative samples compared to preoperativetissue. Moreover, the lnc HOTAIR was significantly higher in the endometrium-induced hydrosalpinx fluidthan in controls (P=0.020), which had a 2.89-fold decrease following salpingectomy (P=0.010).Conclusion: Elevated endometrial lncRNA HOTAIR may disrupt the expression of endometrial receptivity HOXgenes in women with hydrosalpinx. However, our results failed to show a significant inverse correlation between HOTAIRand HOX genes due to limited sample size. Further studies with larger sample sizes are required to investigateHOTAIR inverse co-expression with HOX genes in these subjects.